Application of Morishita Spread Index to temporal and spatial distribution characteristics of landslides in Shanxi and Gansu provinces of China - Wenqiang, Luo; Zhuoyuan, Zhang; Runqiu, Huang (Journal of Nepal Geological Society, 2000)
Morshita Spread Index Iδ was applied for the study of temporal and spatial distribution characteristics of landslides in the Shanxi and Gansu provinces of China. For this purpose, the landslides larger than 105 m3 in volume were considered. In the study area, the spatial distribution of Morishita Spread Index Iδ (l) isgreater than 1 and decreases with increasing mesh scale. Such a trend indicates cluster distribution of landslides. On the other hand, the temporal distribution of Morishita Spread Index Iδ (t) for the above landslides showed a maximum and a minimum, corresponding to the years with high frequency of landslide occurrence.